Analyzing English Textbook through the Lens of Tomlinson’s Theory - Abdul Syahid; Muliana Setia Hapsari ; Siti Anisah ; Tiara Nur Fatimah Almadani; Windy Annastasia Maharani (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study examines the English textbook